Review of Richard H. Jones' Reductionism: analysis and the fullness of reality - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 2005)
The sweep of the book is to argue that reduction (if distinguished from inter-level connections) is not working well anywhere, and if not lower down, there is even less reason to suppose that it will work higher up. Is there anything super-physics, anything super-biological, anything super-psychological, anything super-sociological--and in the end, more generically, anything super-natural, super to the natural? Jones, a lawyer, assesses the strength of evidence on both sides. He has felt the power of encounter with a mysterious universe.
Reductionism: analysis and the fullness of reality - review
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: reductionism; anti-reductionism; naturalism; supernaturalism; analysis; emergence; supervenience; consciousness; spirit